Influence of anatomical factors related to maxillary sinus on outcomes of transcrestal sinus floor elevation - Xiaofei Zheng; Lirong Huang; Si Huang; Anchun Mo; Juanfang Zhu (Elsevier, 2022)
Background/purpose: Graft bone maturation and remodeling in the maxillary sinus require adequate angiogenesis and osteoprogenitor cells migration from the surrounding bony walls and Schneiderian membrane. This study aimed to evaluate the influence of anatomical factors related to maxillary sinus on the outcomes of transcrestal sinus floor elevation using cone-beam computed tomography (CBCT). Materials and methods: Forty-five patients (63 elevated sites) were included in this study. CBCT were obtained preoperatively, immediately and 6 months after surgery. The anatomical features of residual bone height, maxillary sinus width, maxillary sinus angle and Schneiderian membrane thickness were measured on preoperative CBCT. Descriptive statistics and correlation analysis were conducted to evaluate the influence of anatomical factors on outcome parameters, including sinus lift height, graft bone resorption and marginal bone loss. Results: The results showed that there was a positive correlation between sinus width and graft bone resorption. A significantly positive correlation between sinus angle and graft bone resorption was also found. Conclusion: Our findings indicate that the anatomical factors of maxillary sinus (sinus width and sinus angle) have influence on the linear change of bone grafts after transcrestal sinus floor elevation.